RUSSIAN-CHINESE FINANCIAL AND BANKING COOPERATION IN 2022-2023 - Filatov, Maksym (Collection of scientific papers «ΛΌГOΣ», 2024)
This article examines the principal aspects of financial and banking cooperation between the Russian Federation and the People’s Republic of China (PRC) from the onset of the Russian-Ukrainian conflict until the end of 2023. The author underscores the pivotal role of the Chinese government in furnishing economic assistance to Putin’s regime, thereby enabling Mikhail Mishustin’s government to sustain the Russian financial and banking system. Furthermore, the integration of the banking systems of Russia and China and the development of new payment systems between the two countries were also discussed.